Autoconfianza de los estudiantes de Medicina en su interpretación correcta de un electrocardiograma - Gómez M., Patricia; Valdés A., Camila; Yévenes O., Karina; Castro L., Ariel (Revista Hospital Clínico Universidad de Chile, 2016)
Myocardial infarction is a highly prevalent condition. Its early recognition could have a high impact on prognosis. A quick and accurate interpretation of the electrocardiogram (EKG) is crucial to improve the diagnostic and therapeutic processes. Nevertheless, medical literature shows lack of competencies for autonomous and reliable EKG interpretation on both medical students and general practitioners, in many countries. The aim of the present study is to assess the level of self-confidence that medical students from the University of Chile have in their own skills to interpreter EKG rapidly and correctly. With that purpose, an online survey was designed and applied to all medical students from third to 7 th year (final). resUlts: From a total of 1.000 surveys sent, only 206 were completely answered and returned. 77.2 % of these students show very limited self-confidence in their own skills and competences to reliablyinterpret an EKG without anybody else’s help. On the other hand, only 20.9% of them declare to have a high level of self-confidence in this area. We did not find statistically significant differences associated with: gender, educational level, previous academic performance, or campus. conclUsions: Most of our medical students have a low self-confidence level regarding their own capabilities for correctly and quickly “read” an EKG. These findings suggest the need for redesigning the educational strategies currently being used for this purpose, in the undergraduate Cardiology Program, incorporating new teaching methodologies to achieve thedesirable competences needed for correct EKGs’ reading.